A new genus and species of foliicolous lichen in a new family of Strigulales (Ascomycota: Dothideomycetes) reveals remarkable class-level homoplasy - Shu Hua Jiang; David L. Hawksworth; Robert Lücking; Jiang Chun Wei (IMA Fungus)
Abstract Phylogenetic analysis of some foliicolous lichens collected in Hainan Province, China, revealed a new lineage morphologically similar to Porina but phylogenetically related to Strigulaceae (Dothideomycetes), differing from the latter in ascus type. The monospecific genus Tenuitholiascus gen. nov. is introduced for the single species, T. porinoides sp. nov., which is placed in the new, monogeneric family Tenuitholiascaceae, sister to Strigulaceae in Strigulales. The new taxon closely resembles the genus Porina in external morphology and ascospore type, as well as the thin-walled asci and unbranched paraphyses. Yet, it is entirely unrelated to the latter, which belongs in class Lecanoromycetes in the order Gyalectales.